First person - Karen Lange (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Karen Lange is first author on 'Interpreting the pathogenicity of Joubert syndrome missense variants in Caenorhabditis elegans', published in DMM. Karen is a postdoc in the lab of Oliver Blacque at University College Dublin, Dublin, Ireland, using genome-editing techniques in worms to investigate ciliopathies, rare genetic disorders caused by defects in cilia.